Regulations, earnings management, and post-IPO performance: The Chinese evidence - Kao, Jennifer L.; Wu, Donghui; Yang, Zhifeng (Journal of Banking & Finance, 2009)
In this study, we examine whether government regulatory initiatives in China involving IPO by SOEs may have contributed to opportunistic behaviors by the issuer. We focus on two sets of IPO regulations issued between January 1, 1996 and February 11, 1999: pricing regulations, which stipulate that IPO prices be a function of accounting performance, and penalty regulations, which penalize IPO firms for overly optimistic forecasts. We find that IPO firms that report better pricing-period accounting performance have larger declines in post-IPO profitability, lower first-day stock returns and worse long-run post-IPO stock performance. Furthermore, IPO firms that make overoptimistic forecasts also have lower first-day returns and worse post-IPO stock performance. Using non-core earnings as the proxy for earnings management, we document some evidence that IPO firms that report higher pricing-period accounting performance have engaged in more income-increasing earnings management. Hence, pricing regulations may have induced IPO firms to inflate pricing-period earnings and affect the post-IPO performance negatively. On the other hand, penalty regulations have deterred IPO firms from making overoptimistic earnings forecast and therefore have a positive impact on the behavior of IPO firms.